First measurements of velocity-space resolved intra-ELM fast-ion losses on the TCV tokamak - J. Poley-Sanjuán; A. Jansen Van Vuuren; J. Galdón-Quiroga; S. Mazzi; M. Podestà; M.B. Dreval; B.P. Duval; A. Fasoli; A.N. Karpushov; B. Labit; U. Kumar; the EUROfusion Tokamak Exploitation Team; et al. (Nuclear Fusion)
Edge Localised Modes (ELMs) induced fast-ion losses have been characterised in the energy, E , and pitch, $λ = v_\parallel/v$ , space using a unique Fast Ion Loss Detector (FILD) on the tokamak à configuration variable. The FILD is equipped with a 128 Avalanche Photo Diodes (APDs) camera measuring scintillator emission with a 1 MHz bandwidth. The well-defined view lines of the APDs allow for obtaining velocity space information from the emission pattern with unprecedented temporal resolution. Making use of the enhanced FILD capabilities, ELM-induced fast-ion losses were investigated in the ITER Baseline Scenario, mimicking its shape and normalised plasma parameters. Significant fast-ion losses were observed, notably before and during the ELM crashes induced by the presence of a 2/1 MHD instability localised at the plasma’s normalised radius, $ρ \sim 0.7$ . The fast-ion interaction with the plasma instability is concluded to be unconnected to the presence of the ELMs. During the ELM crashes, there is an observed spread in both the fast-ion pitch and energy that reaches higher values (∼ 70 keV) than expected from the pre-ELM fast-ion population, generated by Neutral Beam Injection at ∼27 keV. This implies a fast-ion acceleration during the ELM’s crash. Full orbit neoclassical simulations are used to calculate the neoclassical fast-ion velocity space lost to the FILD and to quantify the neoclassical fast-ion losses.